CESifo World Economic Survey February 2014 - Johanna Plenk; Gernot Nerb; Klaus Wohlrabe; Michael Kleemann (CESifo World Economic Survey, 2014)
World Economic Climate: World economic climate continues to brighten - Economic Expectations: Economic Expectations remain optimistic - Inflation: Inflation expectations remain moderate - Currencies: US Dollar expected to rise - Interest Rates: Long-term interest rates likely to rise - Special Topic: Effects of tapering in the US on the world economy
Keywords: 330; World Economiy Survey; World Economic Climate; Economic Expectations; Inflation; Interest rates; Currencies